MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS LABA SEBAGAI VARIABEL INTERVENING - Freddy Semuel Kawatu (University of Merdeka Malang, 2009)
The objectives of the study were to investigate the relationship between corporate governanceand earnings quality, earnings quality and value of the fi rm, corporate governance mechanismand value of the fi rm, and whether earnings quality was the intervening variable between corporategovernance and value of the fi rm. By using 74 samples and 197 observations, the result indicatedthat fi rst, corporate governance infl uenced earnings quality. (1)Managerial ownership positively influenced earnings quality, (2) Board of commissioner negatively infl uenced earnings quality, (3) Auditcommittee positively infl uenced earnings quality. Second, earnings quality positively infl uenced valueof fi rm. Third, corporate governance mechanism infl uenced value of the fi rm. Finally, the result indicatedthat earnings quality was not the intervening variable between corporate governance mechanismand value of the fi rm.